A Comprehensive Review on the Creation, Description, and Utilization of Surfactants Containing Multiple Hydroxyl Groups - Rakhi Das; Nitesh Mallik; Achyut Adhikari; Ajaya Bhattarai (International Journal of Polymer Science)
The stereoselective synthesis of biobased nonionic sugar surfactants (polyhydroxy surfactants), which are thought to be safer, more affordable, plentiful, biodegradable, biocompatible, and possess mildness and performance in formulation, is becoming increasingly popular as people become more aware of the potential negative effects of conventional surfactants on the environment and human health. Reviewing the stereoselective synthesis of polyhydroxy surfactants is the objective of this article. Additionally, it emphasizes the synthesis and application of sugar-based surfactants in everyday life, as well as their description and the influence of outside factors. A thorough assessment of the literature on biobased polyhydroxy surfactants including alkyl polyglycosides, sorbitol esters, sucrose esters, fatty acid glucamides, and methyl glucosides was studied for methodology. The characterization of the surfactants shows an exponential increase in electrical conductivity when there is an increase in the water volume fraction. The surface tension also showed a linear relationship with surfactant concentration, such that as the concentration increases, the surface tension of the solution decreases. The effect of external parameters on polyhydroxy surfactants was also studied, which shows that increasing temperature favors micellization initiation at a lower concentration. Likewise, the micellar molecular weight and the hydration per unit mass of the surfactants decrease with an increase in the pH value. Evidence to further support these biobased surfactants as substitutes for their petrochemical counterparts is advantageous as worldwide legislation and user requirements for sustainability and safety expand.